2020
DOI: 10.1021/acsabm.0c00202
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term and Clinically Relevant Full-Thickness Human Skin Equivalent for Psoriasis

Abstract: Psoriasis is an incurable, immune-mediated inflammatory disease characterized by the hyperproliferation and abnormal differentiation of keratinocytes. To study in depth the pathogenesis of this disease and possible therapy options suitable, pre-clinical models are required. Three-dimensional skin equivalents are a potential alternative to simplistic monolayer cultures and immunologically different animal models. However, current skin equivalents lack long-term stability, which jeopardizes the possibility to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…To fabricate the scaffold-free breast cancer model, we utilized the layer-by-layer ECM coating and accumulation technique. Normal fibroblasts (NFs) were coated with fibronectin (FN) and gelatin (G) proteins to form nano-layer of ECM moieties around the cells 28 . The coated individual NFs were mixed with HUVECs and MDA-MB231 BCCs followed by accumulation in a cell-culture insert.…”
Section: Resultsmentioning
confidence: 99%
“…To fabricate the scaffold-free breast cancer model, we utilized the layer-by-layer ECM coating and accumulation technique. Normal fibroblasts (NFs) were coated with fibronectin (FN) and gelatin (G) proteins to form nano-layer of ECM moieties around the cells 28 . The coated individual NFs were mixed with HUVECs and MDA-MB231 BCCs followed by accumulation in a cell-culture insert.…”
Section: Resultsmentioning
confidence: 99%
“…Normal fibroblasts (NFs) were coated with fibronectin (FN) and gelatin (G) proteins to form nano-layer of ECM moieties around the cells. 20, 28 The coated individual NFs were mixed with HUVECs and MDA-MB231 BCCs followed by accumulation in a cell-culture insert. We observed that MDA-MB231 morphology was altered in 3-D scaffold-free tissues as compared to 2-D culture (Figure 1a, b, e) .…”
Section: Resultsmentioning
confidence: 99%
“…The assembled tissue was cultured for 7 days (37°C, 5% CO 2 ) with a change of media every other day. Fibronectin/gelatin-coated cells accumulate to form thick vascularized scaffold-free connective tissues ( 41 , 42 ).…”
Section: Methodsmentioning
confidence: 99%